Kajian Tanam Sistem Sonor terhadap Varietas Unggul Padi di Lahan Pasang Surut Sumatera Selatan (Studi Kasus di Daerah Pasang Surut Telang) - NP. Sri Ratmini; Yohanes Yohanes (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
Sonor system (direct seeding) was practiced by rice farmers in tidal land. Â Labor was one of the limiting factors in the farming system in tidal land. Implementation of the system can save labor cost. The purpose of this study was to see the level of adaptation and productivity of some new varieties of the sonor system technology. The study was conducted in tidal land typology of potential acid sulphate in Mukti Jaya Village, Muara Telang Sub-District, Banyuasin District in 2011/2012 planting season. Varieties tested were new varieties, namely Inpari 4, Inpari 10, Inpari 11, Inpari 13, Mekongga and Ciherang as the control. The observations were conducted at 3 fields as replication. The study showed that all the new varieties tested indicated high adaptability to the sonor system and the production has approached potential results. Â Varieties with the highest production were Inpari 10 and Inpari 13 of Â 8.35 t/ha and 8.19 t/ha respectively.